Association of symptom severity, pain and other behavioral and medical comorbidities with diverse measures of functioning among adults with post-traumatic stress disorder. (February 2021) - Manhapra, Ajay; Stefanovics, Elina A.; Rhee, Taeho Greg; Rosenheck, Robert A.
Abstract: Post-traumatic stress disorder (PTSD) is an often disabling mental disorder whose management typically focuses on reducing PTSD symptoms. Chronic pain and other comorbidities that commonly accompany PTSD symptoms may also be independently associated with disability. Using data from the 2012–2013 National Epidemiologic Survey on Alcohol and Related Conditions, we examined the independent association of PTSD symptom severity, pain interference, non-PTSD psychiatric and substance use disorders (SUD), and medical illnesses with each of four domains of function: mental health-related quality of life and physical functioning assessed with the Mental Health Composite Score (MCS) and Physical Function Score (PFS) of the Short Form-12; perceived social support from the Interpersonal Support and Evaluation List-12 (ISEL-12); and self-reported past year employment. Among 1779 individuals representing 11 million U.S. adults who met the Diagnostic and Statistical Manual-5 (DSM-5) criteria for Past Year PTSD, the MCS (41.2; SD 12.5), PFS (44.8; SD 13.2) and ISEL-12 (33.6; SD 7.2) indicated substantial disability when compared to population norms, and only 63.6% were employed. Multiple regression showed the MCS had a modest negative association with PTSD symptoms, pain interference, psychiatric multimorbidity and medical comorbidity although not with SUD. PFS and employment had significant negative associations with pain interference and medical comorbidity. ISEL-12 had a weak negative association with PTSD symptoms and non-PTSD psychiatric comorbidity. Common comorbidities thus significantly influence disability associated with PTSD, often more strongly than PTSD symptoms. PTSD treatment may require integrative multimorbidity management beyond a focus on PTSD symptoms. Highlights: In a national sample of patients with PTSD, we observed high prevalence of comorbidities and pain interference along with profound disability. Comorbidities and pain interference had similar or larger negative associations than PTSD symptoms with mental well-being. Pain interference and medical co-morbidity dominated negative relationships with physical wellbeing and employment. SSubstance use disorders had minimal association only with employment.